Cluster Conversation: Umar Timol and Prof. Dr. Ute Fendler (A Conversation with ..., 2024)
Mauritian writer and photographer Umar Timol joined the Cluster of Excellence to observe and accompany the Cluster's acitivities and events in the month of May 2024. In this interview, he talks with Prof. Dr. Ute Fendler about his extensive body of work. ***** L'écrivain et photographe mauricien Umar Timol a rejoint le Pôle d'excellence pour observer et accompagner les activités et événements du Pôle au mois de mai 2024. Dans cette interview, il s'entretient avec le professeur Ute Fendler au sujet de son vaste corpus d'œuvres.